(3fRgI GdNGWQ aj hVY MOhO Ydi RGO GdeSGaQs - (3eMeO Hf CHi GdNjQ GdMSfj GdeGdcjs; (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3Efi bO GSJNQJ Gddg JYGdi ai MOhO JJYdb HRGO GdeSGaQ aeG de jcf ePchQkG ai daX GdLhGgQ s
(3BNQgG (B:s
(3hcd KdGKg CejGd aQSN hcd OQLg JeSM ef GdBQV (B56 (3ejdG hKdKi ejd Je hGdMeO ddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B358 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B103 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs